2008
DOI: 10.1021/es801591k
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Stable Isotope Fractionation during Reduction of Hg(II) by Different Microbial Pathways

Abstract: Mercury (Hg) stable isotope fractionation has recently been developed as a tool in biogeochemistry. In this study, the extent of Hg stable isotope fractionation during reduction of ionic mercury [Hg(II)] by two Hg(II)-resistant strains, Bacillus cereus 5 and the thermophile Anoxybacillus sp. FB9 [which actively detoxify Hg(II) by the mer system] and a Hg(II)-sensitive metal-reducing anaerobe, Shewanella oneidensis MR-1 [which reduces Hg(II) at low concentrations], was investigated. In all cases, barring suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
162
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 26 publications
12
162
4
Order By: Relevance
“…As described previously, 500-600 ml of autoclaved medium components (except as noted below) were assembled aerobically in a pre-sterilized 1 L reactor, and the assay medium was bubbled with N 2 for 45 min to purge any dissolved O 2 (Kritee et al, 2008). To initiate the assays, cell pellets from starter cultures were re-suspended in the assay medium and were also bubbled with N 2 for 45 min.…”
Section: Reactor Assembly and Assay Conditionsmentioning
confidence: 99%
“…As described previously, 500-600 ml of autoclaved medium components (except as noted below) were assembled aerobically in a pre-sterilized 1 L reactor, and the assay medium was bubbled with N 2 for 45 min to purge any dissolved O 2 (Kritee et al, 2008). To initiate the assays, cell pellets from starter cultures were re-suspended in the assay medium and were also bubbled with N 2 for 45 min.…”
Section: Reactor Assembly and Assay Conditionsmentioning
confidence: 99%
“…However, only a few have been characterized in any detail. Early studies focusing on processes only found mass dependent fractionation (MDF), such as volatilization of dissolved gaseous mercury (Zheng et al, 2007) and microbial reduction of Hg(II) (Kritee et al, 2007(Kritee et al, , 2008. Evidence of mass independent fractionation (MIF) was recently observed in various aquatic food web organisms (Jackson et al, 2008), fish , mosses and peat cores (Ghosh et al, 2008), and coal deposits (Biswas et al, 2008), suggesting that MIF of Hg can be caused by natural processes, such as photoreduction and liquid-vapour evaporation (Estrade et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hg isotopic signature, a powerful tool for the investigation of biogeochemical processes and the potential identification of pollution sources Perrot et al, 2010;Sonke, 2011), can also be used to investigate biological processes Kritee et al, 2008;Kwon et al, 2012;Perrot et al, 2015;Rodƕiguez-GonĆșalez et al, 2009 ) that can undergo mass dependent fractionation (MDF) due to specific reactions like methylation/ demethylation, reduction as well as transport and metabolic processes (Bergquist and Blum, 2007;Kritee et al, 2008;Yin et al, 2010Yin et al, , 2013b. Hg can additionally exhibit mass independent fractionation (MIF) (Bergquist and Blum, 2007).…”
Section: Introductionmentioning
confidence: 99%